Optical glass, glass preform, glass element and apparatus

CN123003141APending Publication Date: 2026-10-30CDGM OPTICAL GLASS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611387841.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0025]本发明的有益效果是:通过合理的组分设计,本发明光学玻璃在具有较高的硬度的同时,还具有优异的光透过率,满足高性能设备的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides an optical glass, which comprises the following components in percentage by weight: SiO2: 42.5-54%; B2O3: 5.5-17.5%; TiO2: 3-15%; ZnO: 0.1-8%; Na2O: 2-14%; CaO: 6-18%, wherein (CaO+B2O3) / SiO2 is 0.28-0.80. Through reasonable component design, the optical glass has high hardness and excellent light transmittance, and meets the application of high-performance equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an optical glass, and more particularly to an optical glass with high hardness and excellent light transmittance, as well as glass preforms, glass elements and devices made therefrom. Background Technology

[0002] In recent years, with the rapid development of technologies such as surveillance and security, vehicle imaging, and smartphones, the demand for optical components used in these devices has continued to increase. Among optical glass used to manufacture glass components, those with a refractive index (n) of 1.560–1.640 that can achieve chromatic aberration correction are particularly important. d ) and Abbe numbers (ν) of 43.0–49.0 d The demand for medium-refractive-index, low-dispersion glass has become extremely high. With the continuous development of the imaging field, the requirements for high-definition imaging are also increasing. In fields such as automotive imaging, security surveillance, and photography, the clearer the captured image, the more information can be extracted. This necessitates using optical glass with the highest possible light transmittance. Simultaneously, automotive imaging and security surveillance applications place high demands on the hardness of the optical glass used. High hardness helps resist wear and tear from sand and gravel during vehicle operation, extending its service life. Summary of the Invention

[0003] The technical problem to be solved by the present invention is to provide an optical glass with high hardness and excellent light transmittance, as well as glass preforms, glass components and devices made therefrom.

[0004] The technical solution adopted by this invention to solve the technical problem is:

[0005] (1) Optical glass, the composition of which is expressed as a weight percentage, contains: SiO2: 42.5%~54%; B2O3: 5.5%~17.5%; TiO2: 3%~15%; ZnO: 0.1%~8%; Na2O: 2%~14%; CaO: 6%~18%, of which (CaO+B2O3) / SiO2 is 0.28~0.80.

[0006] (2) The optical glass according to (1) further comprises, by weight percentage: Li2O: 0-7%; and / or K2O: 0-7%; and / or MgO: 0-5%; and / or SrO: 0-5%; and / or BaO: 0-5%; and / or ZrO2: 0-5%; and / or Al2O3: 0-6%; and / or Nb2O5: 0-3%; and / or WO3: 0-3%; and / or Ln2O3: 0-3%; and / or clarifying agent: 0-1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0007] (3) Optical glass containing SiO2, B2O3, TiO2, ZnO, Na2O and CaO, the composition of which is expressed as a weight percentage, wherein (CaO+B2O3) / SiO2 is 0.28 to 0.80, and the refractive index n of the optical glass is... d The Abbe number ν ranges from 1.560 to 1.640. d Its S value is 43.0–49.0, and its Knoop hardness is 530 × 10⁻⁶. 7 Above Pa, chromaticity λ 80 The wavelength is below 400nm, and the chromaticity λ5 is below 360nm.

[0008] (4) The optical glass according to (3) comprises, by weight percentage: SiO2: 42.5%–54%; and / or B2O3: 5.5%–17.5%; and / or TiO2: 3%–15%; and / or ZnO: 0.1%–8%; and / or Na2O: 2%–14%; and / or CaO: 6%–18%; and / or Li2O: 0%–7%; and / or K2O: 0%–7%; and / or MgO: 0%–5%; and / or SrO: 0–5%; and / or BaO: 0–5%; and / or ZrO2: 0–5%; and / or Al2O3: 0–6%; and / or Nb2O5: 0–3%; and / or WO3: 0–3%; and / or Ln2O3: 0–3%; and / or clarifying agent: 0–1%, wherein Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0009] (5) The optical glass according to any one of (1) to (4), wherein the composition, expressed as a weight percentage, satisfies one or more of the following conditions:

[0010] 1) The ratio of (CaO+B2O3) / SiO2 is 0.35 to 0.75, preferably 0.40 to 0.65;

[0011] 2) The CaO / B2O3 ratio is 0.40 to 2.50, preferably 0.50 to 2.00, more preferably 0.60 to 1.60, and even more preferably 0.80 to 1.20;

[0012] 3) The CaO / TiO2 ratio is 0.50 to 3.00, preferably 0.60 to 2.80, more preferably 0.80 to 2.00, and even more preferably 1.00 to 1.60;

[0013] 4) The ratio of (ZnO+BaO+SrO) / B2O3 is 0.05 to 1.00, preferably 0.10 to 0.80, and more preferably 0.15 to 0.50.

[0014] 5) The ratio of (ZrO2+Nb2O5+WO3) / ZnO is 1.00 or less, preferably 0.70 or less, and more preferably 0.05 to 0.50.

[0015] 6) The ratio of (Li2O+Na2O+K2O) / TiO2 is 0.30~4.00, preferably 0.50~3.00, more preferably 0.80~2.50, and even more preferably 1.00~1.80;

[0016] 7) The ratio of (Li2O+Na2O+K2O) / CaO is 0.30~2.50, preferably 0.50~2.00, more preferably 0.60~1.60, and even more preferably 0.80~1.20;

[0017] 8) The ratio of (ZnO+BaO+SrO+MgO) / SiO2 is 0.01 to 0.40, preferably 0.03 to 0.30, and more preferably 0.05 to 0.15;

[0018] 9) The Li2O / Al2O3 ratio is 0.05 to 5.00, preferably 0.10 to 3.00, and more preferably 0.50 to 1.50;

[0019] 10) (TiO2+ZnO) / (Li2O+K2O) is 1.00~6.00, preferably (TiO2+ZnO) / (Li2O+K2O) is 1.50~5.00, more preferably (TiO2+ZnO) / (Li2O+K2O) is 2.00~4.50, and even more preferably (TiO2+ZnO) / (Li2O+K2O) is 2.50~4.00.

[0020] (6) The optical glass according to any one of (1) to (4), wherein the composition is expressed as a weight percentage, wherein: SiO2: 44% to 52%, preferably SiO2: 46% to 49.5%; and / or B2O3: 8% to 16%, preferably B2O3: 10.5% to 14.5%; and / or TiO2: 5% to 14%, preferably TiO2: 7% to 12%; and / or ZnO: 1% to 7%, preferably ZnO: 2% to 5%; and / or Li2O Li₂O: 0.1%–4.5%, preferably Li₂O: 0.5%–3.5%; and / or Na₂O: 4%–12%, preferably Na₂O: 6%–9.8%; and / or K₂O: 0.1%–4.5%, preferably K₂O: 0.5%–3.5%; and / or MgO: 0%–3%, preferably MgO: 0%–2%, more preferably MgO-free; and / or CaO: 8%–16%, preferably CaO: 10.1%–14.5%; and / or SrO: 0-3%, preferably SrO: 0-2%, more preferably without SrO; and / or BaO: 0-3%, preferably BaO: 0-2%, more preferably without BaO; and / or ZrO2: 0-3%, preferably ZrO2: 0.1%-2%; and / or Al2O3: 0.1%-4.5%, preferably Al2O3: 0.5%-3.5%; and / or Nb2O5: 0-2%, preferably Nb2O5: 0-1%, more preferably without Nb2O5; And / or WO3: 0-2%, preferably WO3: 0-1%, more preferably WO3-free; and / or Ln2O3: 0-2%, preferably Ln2O3: 0-1%, more preferably Ln2O3-free; and / or clarifying agent: 0-0.5%, preferably 0-0.3%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

[0021] (7) The optical glass according to any one of (1) to (4), wherein the refractive index n of the optical glass is d The value is 1.560–1.640, preferably 1.570–1.630, more preferably 1.585–1.620; and / or the Abbe number ν. dThe value is 43.0 to 49.0, preferably 44.0 to 48.0, more preferably 45.0 to 47.0; and / or the chromaticity λ 80 The wavelength is 400 nm or less, preferably 390 nm or less, more preferably 385 nm or less; and / or the tinting strength λ5 is 360 nm or less, preferably 355 nm or less, more preferably 350 nm or less; and / or the Knoop hardness is 530 × 10⁻⁶. 7 Pa or higher, preferably 550 × 10⁻⁶ Pa. 7 Pa or higher, more preferably 570 × 10 Pa 7 Pa or above; and / or coefficient of thermal expansion α -30℃ / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below; and / or water resistance stability of Class 2 or above, preferably Class 1; and / or acid resistance stability of Class 2 or above, preferably Class 1; and / or weather resistance of Class 2 or above, preferably Class 1; and / or density of 3.00 g / cm³. 3 The preferred value is 2.90 g / cm³. 3 The following is a preferred value: 2.80 g / cm³ 3 The following are also considered: a transition temperature of 570°C or less, preferably 560°C or less, more preferably 520°C to 555°C; an abrasion degree of 110 to 145, preferably 115 to 140, more preferably 120 to 135; a Young's modulus of 86.0 GPa or more, preferably 90.0 GPa or more, more preferably 92.0 GPa or more; and / or a bubble degree of A grade or more, preferably A0 grade or more, more preferably A 00 Grade; and / or stripe density of grade D or above, preferably grade C or above, more preferably grade B or above.

[0022] (8) Glass preforms, made of any one of the optical glass described in (1) to (7).

[0023] (9) A glass element made of any one of the optical glass described in (1) to (7) or made of the glass preform described in (8).

[0024] (10) An apparatus comprising the optical glass of any one of (1) to (7) and / or the glass element of (9).

[0025] The beneficial effects of this invention are: through reasonable component design, the optical glass of this invention has high hardness and excellent light transmittance, which meets the application requirements of high-performance equipment. Detailed Implementation

[0026] The embodiments of the optical glass of the present invention will now be described in detail. However, the present invention is not limited to the embodiments described below, and appropriate modifications can be made to implement it within the scope of the purpose of the present invention. Furthermore, regarding repeated descriptions, although there are appropriate omissions, this will not limit the spirit of the invention. In the following text, the optical glass of the present invention may be simply referred to as glass.

[0027] Optical Glass

[0028] The composition range of each component (ingredient) of the optical glass of the present invention will be described below. In the present invention, unless otherwise specified, the content of each component, the total content, and the total content are all expressed as weight percentages (wt%), that is, the weight percentage of the content of each component, the total content, and the total content relative to the total amount of glass material converted into oxide composition. Here, "converted into oxide composition" means that when the oxides, complex salts, and hydroxides used as raw materials for the optical glass of the present invention decompose and transform into oxides upon melting, the total amount of such oxides is taken as 100%.

[0029] Unless otherwise specified in the specific context, the numerical ranges listed in this invention include upper and lower limits, and "above" and "below" include endpoint values ​​and all integers and fractions included in the range, but are not limited to the specific values ​​listed when the range is defined. The term "and / or" as used herein is inclusive; for example, "A and / or B" means only A, or only B, or both A and B.

[0030] <Essential and Optional Components>

[0031] SiO2 is the framework of the glass of this invention. It can increase the viscosity of the molten glass, improve the glass's resistance to devitrification and chemical stability, and reduce the glass's abrasion resistance. However, if its content is too high, the difficulty of melting the glass increases, the transition temperature rises, and the refractive index decreases. Therefore, the SiO2 content in this invention is 42.5% to 54%, preferably 44% to 52%, and more preferably 46% to 49.5%. In some embodiments, the SiO2 content can be 42.5%, 43%, 43.5%, 44%, 44.5%, 45%, 45.5%, 46%, 46.5%, 47%, 47.5%, 48%, 48.5%, 49%, 49.5%, 50%, 50.5%, 51%, 51.5%, 52%, 52.5%, 53%, 53.5%, 54%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0032] B2O3 is a component of the glass network forging system, which can improve the stability, melt flow, and resistance to crystallization of glass. However, if the B2O3 content is too high, the chemical stability and mechanical properties of the glass will decrease, and the devitrification resistance will decline. Therefore, the B2O3 content in this invention is 5.5% to 17.5%, preferably 8% to 16%, and more preferably 10.5% to 14.5%. In some embodiments, the B2O3 content can be 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0033] TiO2 can improve the refractive index and dispersion of glass, and enhance its resistance to crystallization and stability. However, if its content is too high, the light transmittance of the glass will decrease, and the refractive index and Abbe number will easily exceed design requirements. Therefore, the TiO2 content in this invention is 3% to 15%, preferably 5% to 14%, and more preferably 7% to 12%. In some embodiments, the TiO2 content can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0034] ZnO can improve the chemical stability and melt properties of glass, which is beneficial for reducing the glass transition temperature and coefficient of thermal expansion. However, when its content is too high, the glass's devitrification resistance decreases. Therefore, the ZnO content in this invention is 0.1% to 8%, preferably 1% to 7%, and more preferably 2% to 5%. In some embodiments, the ZnO content can be 0.1%, 0.3%, 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, 7.3%, 7.5%, 7.7%, 8%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0035] Li₂O can lower the glass transition temperature, adjust the high-temperature viscosity of glass, and improve the melting properties of glass. However, high Li₂O content is detrimental to the chemical stability and cost economy of glass raw materials, and can also lead to excessively low refractive index of glass. Therefore, the Li₂O content in this invention is 0–7%, preferably 0.1%–4.5%, and more preferably 0.5%–3.5%. In some embodiments, the Li₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0036] Na₂O can adjust the optical constants of glass, improving its melting properties, transition temperature, and light transmittance. However, if its content is too high, the coefficient of thermal expansion of the glass increases, and its chemical stability decreases. Therefore, the Na₂O content is 2% to 14%, preferably 4% to 12%, and more preferably 6% to 9.8%. In some embodiments, the Na₂O content can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0037] K₂O improves the thermal stability and melt permeability of glass, but if its content is too high, the glass's resistance to devitrification and chemical stability deteriorates. Therefore, the K₂O content in this invention is 0-7%, preferably 0.1%-4.5%, and more preferably 0.5%-3.5%. In some embodiments, the K₂O content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.3%, 0.5%, 0.7%, 1%, 1.3%, 1.5%, 1.7%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, 6.3%, 6.5%, 6.7%, 7%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0038] In some embodiments, by controlling the ratio (Li2O+Na2O+K2O) / TiO2 between the total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) and the content of TiO2 (Li2O+Na2O+K2O) in the range of 0.30 to 4.00, the optical glass can more easily obtain the desired optical constant while improving the streaking of the glass. Therefore, it is preferable that (Li2O+Na2O+K2O) / TiO2 is 0.30 to 4.00, more preferably (Li2O+Na2O+K2O) / TiO2 is 0.50 to 3.00, further preferably (Li2O+Na2O+K2O) / TiO2 is 0.80 to 2.50, and even more preferably (Li2O+Na2O+K2O) / TiO2 is 1.00 to 1.80. In some implementations, the value of (Li₂O+Na₂O+K₂O) / TiO₂ can be 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70 The values ​​are 2.75, 2.80, 2.85, 2.90, 2.95, 3.00, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30, 3.35, 3.40, 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0039] In some embodiments, by controlling the ratio (TiO2+ZnO) / (Li2O+K2O) between the total content of TiO2 and ZnO (TiO2+ZnO) and the total content of Li2O and K2O (Li2O+K2O) in the range of 1.00 to 6.00, the water resistance of the glass can be improved while preventing an increase in the coefficient of thermal expansion of the glass. Therefore, it is preferable that (TiO2+ZnO) / (Li2O+K2O) is 1.00 to 6.00, more preferably (TiO2+ZnO) / (Li2O+K2O) is 1.50 to 5.00, further preferably (TiO2+ZnO) / (Li2O+K2O) is 2.00 to 4.50, and even more preferably (TiO2+ZnO) / (Li2O+K2O) is 2.50 to 4.00. In some implementations, the value of (TiO2+ZnO) / (Li2O+K2O) can be 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85, 1.90, 1.95, or 2.00. 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00, 3.05, 3.10, 3.15, 3.20, 3.25, 3.30, 3.35, 3.40 3.45, 3.50, 3.55, 3.60, 3.65, 3.70, 3.75, 3.80, 3.85, 3.90, 3.95, 4.00, 4.05, 4.10, 4.15, 4.20, 4.25, 4.30, 4.35, 4.40, 4.45, 4.50, 4.55, 4.60, 4.65, 4.70, 4.75, 4.80 The values ​​are 4.85, 4.90, 4.95, 5.00, 5.05, 5.10, 5.15, 5.20, 5.25, 5.30, 5.35, 5.40, 5.45, 5.50, 5.55, 5.60, 5.65, 5.70, 5.75, 5.80, 5.85, 5.90, 5.95, 6.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0040] MgO can adjust the refractive index and melt flow properties of glass, but if the MgO content is too high, the glass's devitrification resistance and stability decrease. Therefore, the MgO content is 0-5%, preferably 0-3%, and more preferably 0-2%. In some embodiments, it is further preferred that the glass does not contain MgO. In some embodiments, the MgO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0041] CaO can improve the devitrification resistance and chemical stability of glass, and is beneficial for reducing glass density. However, if its content is too high, the glass's resistance to crystallization decreases. Therefore, the CaO content is 6% to 18%, preferably 8% to 16%, and more preferably 10.1% to 14.5%. In some embodiments, the CaO content can be 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.1%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0042] In some embodiments, controlling the ratio of CaO content to B2O3 content (CaO / B2O3) within the range of 0.40 to 2.50 can improve the bubble content of the glass and prevent its weather resistance from deteriorating. Therefore, a CaO / B2O3 ratio of 0.40 to 2.50 is preferred, 0.50 to 2.00 is more preferred, 0.60 to 1.60 is even more preferred, and 0.80 to 1.20 is still more preferred. In some implementations, the CaO / B2O3 value can be 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1 0.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0043] In some embodiments, controlling the CaO / TiO2 ratio (CaO / TiO2) within the range of 0.50 to 3.00 can reduce the glass transition temperature while preventing a deterioration in the glass's water resistance. Therefore, a CaO / TiO2 ratio of 0.50 to 3.00 is preferred, more preferably 0.60 to 2.80, even more preferably 0.80 to 2.00, and still more preferably 1.00 to 1.60. In some implementations, the CaO / B2O3 value can be 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1 0.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, 2.55, 2.60, 2.65, 2.70, 2.75, 2.80, 2.85, 2.90, 2.95, 3.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0044] In some embodiments, by controlling the ratio of the total content of Li2O, Na2O, and K2O (Li2O+Na2O+K2O) to the content of CaO (Li2O+Na2O+K2O) / CaO within the range of 0.30 to 2.50, the Young's modulus of the glass can be increased while the density of the glass is reduced. Therefore, it is preferable that (Li2O+Na2O+K2O) / CaO is 0.30 to 2.50, more preferably (Li2O+Na2O+K2O) / CaO is 0.50 to 2.00, further preferably (Li2O+Na2O+K2O) / CaO is 0.60 to 1.60, and even more preferably (Li2O+Na2O+K2O) / CaO is 0.80 to 1.20. In some implementations, the value of (Li₂O + Na₂O + K₂O) / CaO can be 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1.35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.05, 2.10, 2.15, 2.20, 2.25, 2.30, 2.35, 2.40, 2.45, 2.50, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0045] In some embodiments, the ratio of the total content of CaO and B2O3 (CaO+B2O3) to the content of SiO2 (CaO+B2O3) / SiO2 is controlled within the range of 0.28 to 0.80. This can improve the hardness of the glass while preventing a decrease in its light transmittance. Therefore, it is preferable that (CaO+B2O3) / SiO2 is 0.28 to 0.80, more preferably 0.35 to 0.75, and even more preferably 0.40 to 0.65. In some implementations, the value of (CaO+B2O3) / SiO2 can be 0.28, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, etc., as well as all ranges and subranges between the above values. It should be understood that, in implementations, any of the above ranges can be combined with any other range.

[0046] SrO can adjust the refractive index and Abbe number of glass, and improve its meltability. However, if its content is too high, the chemical stability and resistance to crystallization of the glass will decrease. Therefore, the SrO content is 0-5%, preferably 0-3%, and more preferably 0-2%. In some embodiments, it is further preferred that no SrO is present. In some embodiments, the SrO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0047] BaO can adjust the refractive index and Abbe number of glass, and optimize the coefficient of thermal expansion of glass. If its content is too high, the weather resistance and chemical stability of glass will deteriorate. Therefore, the BaO content is 0-5%, preferably 0-3%, and more preferably 0-2%. In some embodiments, it is further preferred that BaO is not present. In some embodiments, the BaO content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0048] In some embodiments, by controlling the ratio of the total content of ZnO, BaO, and SrO (ZnO+BaO+SrO) to the content of B2O3 (ZnO+BaO+SrO) / B2O3 within the range of 0.05 to 1.00, the Young's modulus of the glass can be increased while reducing the coefficient of thermal expansion. Therefore, it is preferable that (ZnO+BaO+SrO) / B2O3 is 0.05 to 1.00, more preferably (ZnO+BaO+SrO) / B2O3 is 0.10 to 0.80, and even more preferably (ZnO+BaO+SrO) / B2O3 is 0.15 to 0.50. In some implementations, the value of (ZnO+BaO+SrO) / B2O3 can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0049] In some embodiments, by controlling the ratio (ZnO+BaO+SrO+MgO) / SiO2 between the total content of ZnO, BaO, SrO, and MgO (ZnO+BaO+SrO+MgO) and the content of SiO2 (ZnO+BaO+SrO+MgO) / SiO2 within the range of 0.01 to 0.40, the anti-crystallization properties of the glass can be improved while optimizing the abrasion resistance, which is beneficial for glass grinding. Therefore, it is preferable that (ZnO+BaO+SrO+MgO) / SiO2 is 0.01 to 0.40, more preferably (ZnO+BaO+SrO+MgO) / SiO2 is 0.03 to 0.30, and even more preferably (ZnO+BaO+SrO+MgO) / SiO2 is 0.05 to 0.15. In some implementations, the value of (ZnO+BaO+SrO+MgO) / SiO2 can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0050] ZrO2 can improve the refractive index and devitrification resistance of glass, as well as its chemical stability and mechanical properties. However, if its content is too high, the melting difficulty of the glass increases, making it prone to inclusions and a decrease in light transmittance, while also reducing the glass's resistance to crystallization. Therefore, the ZrO2 content in this invention is 0-5%, preferably 0-3%, and more preferably 0.1%-2%. In some embodiments, the ZrO2 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0051] Al2O3 can improve the resistance to crystallization and thermal stability of glass, but if its content is too high, it will lead to an increase in the glass transition temperature and a decrease in the glass's meltability. Therefore, the content of Al2O3 in this invention is 0-6%, preferably 0.1%-4.5%, and more preferably 0.5%-3.5%. In some embodiments, the content of Al2O3 can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.3%, 3.5%, 3.7%, 4%, 4.3%, 4.5%, 4.7%, 5%, 5.3%, 5.5%, 5.7%, 6%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0052] In some embodiments, controlling the ratio of Li₂O content to Al₂O₃ content (Li₂O / Al₂O₃) within the range of 0.05 to 5.00 can improve the Young's modulus of the glass while preventing a decrease in its acid resistance. Therefore, a Li₂O / Al₂O₃ ratio of 0.05 to 5.00 is preferred, a Li₂O / Al₂O₃ ratio of 0.10 to 3.00 is more preferred, and a Li₂O / Al₂O₃ ratio of 0.50 to 1.50 is even more preferred. In some implementations, the Li₂O / Al₂O₃ value can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, 0.37, 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, 1.03, 1.05, 1.07, 1.10, 1.13, 1.15, 1.17, 1.20, 1.23, 1.25, 1.27, 1.30, 1.33, 1. 35, 1.37, 1.40, 1.43, 1.45, 1.47, 1.50, 1.53, 1.55, 1.57, 1.60, 1.63, 1.65, 1.67, 1.70, 1.73, 1.75, 1.77, 1.80, 1.83, 1.85, 1.87, 1.90, 1.93, 1.95, 1.97, 2.00, 2.10, 2.20, 2.30, 2.4 0, 2.50, 2.60, 2.70, 2.80, 2.90, 3.00, 3.10, 3.20, 3.30, 3.40, 3.50, 3.60, 3.70, 3.80, 3.90, 4.00, 4.10, 4.20, 4.30, 4.40, 4.50, 4.60, 4.70, 4.80, 4.90, 5.00, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0053] Nb₂O₅ can adjust the refractive index and dispersion of glass, improving its thermal stability and devitrification resistance. However, if its content is too high, the light transmittance and anti-crystallization properties of the glass will decrease. Therefore, the Nb₂O₅ content is 0–3%, preferably 0–2%, and more preferably 0–1%. In some embodiments, it is further preferred that the glass does not contain Nb₂O₅. In some embodiments, the Nb₂O₅ content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0054] WO3 can adjust the refractive index and dispersion of glass. If the WO3 content is too high, the thermal stability of the glass decreases, and the resistance to devitrification and light transmittance decrease. Therefore, the WO3 content is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that the glass does not contain WO3. In some embodiments, the WO3 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0055] In some embodiments, the ratio of the total content of ZrO2, Nb2O5, and WO3 (ZrO2+Nb2O5+WO3) to the content of ZnO (ZrO2+Nb2O5+WO3) / ZnO is controlled below 1.00. This prevents the glass from exhibiting poor bubble density and weather resistance, allowing the glass to simultaneously possess good bubble density and excellent weather resistance. Therefore, it is preferable that (ZrO2+Nb2O5+WO3) / ZnO is below 1.00, more preferably below 0.70, and even more preferably between 0.05 and 0.50. In some implementations, the value of (ZrO2+Nb2O5+WO3) / ZnO can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.13, 0.15, 0.17, 0.20, 0.23, 0.25, 0.27, 0.30, 0.33, 0.35, or 0.37. The ranges are 0.40, 0.43, 0.45, 0.47, 0.50, 0.53, 0.55, 0.57, 0.60, 0.63, 0.65, 0.67, 0.70, 0.73, 0.75, 0.77, 0.80, 0.83, 0.85, 0.87, 0.90, 0.93, 0.95, 0.97, 1.00, and all ranges and subranges between these values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0056] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3) can improve the refractive index and devitrification resistance of glass. By controlling the Ln2O3 content to below 3%, the chemical stability of the glass can be prevented from decreasing. Therefore, the Ln2O3 content in this invention is 0-3%, preferably 0-2%, and more preferably 0-1%. In some embodiments, it is further preferred that Ln2O3 is not present. In some embodiments, the Ln2O3 content can be 0, greater than 0, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.3%, 2.5%, 2.7%, 3%, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation plan, any of the above scopes can be combined with any other scopes.

[0057] In this invention, by using one or more components selected from Sb₂O₃, SnO₂, and CeO₂ as a clarifying agent containing 0-1%, the clarification effect of the glass can be improved and the bubble content of the glass optimized. Preferably, the content of the clarifying agent is 0-0.5%, more preferably 0-0.3%. In some embodiments, the content of the clarifying agent can be 0, greater than 0, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0058] <Components that should not be present>

[0059] In the glass of this invention, even if oxides of transition metals such as V, Cr, Mn, Fe, Co, Ni, Cu, Ag, and Mo are contained in small amounts, either alone or in combination, the glass will be colored and absorb at specific wavelengths in the visible light region, thereby weakening the property of this invention to improve visible light transmittance. Therefore, it is preferable that the glass does not contain these oxides, especially for optical glass where transmittance in the visible light region is required.

[0060] Oxides of Th, Cd, Tl, Os, Be, and Se have been increasingly subject to controlled use in recent years due to their status as hazardous chemicals. Environmental protection measures are essential not only in glass manufacturing but also in processing and post-product disposal. Therefore, given the importance of environmental impact, it is preferable to avoid the presence of these substances, except where their contamination is unavoidable. As a result, the optical glass becomes virtually free of pollutants. Therefore, the optical glass of this invention can be manufactured, processed, and disposed of even without special environmental countermeasures.

[0061] To achieve environmental friendliness, the optical glass of the present invention preferably does not contain As2O3 and PbO.

[0062] The terms "not containing" and "0" used herein mean that the compound, molecule, or element was not intentionally added to the optical glass of this invention as a raw material; however, as raw materials and / or equipment used in the production of optical glass, there may be certain unintentionally added impurities or components that may be present in small or trace amounts in the final optical glass, and such cases are also within the scope of protection of this patent.

[0063] The performance of the optical glass of the present invention will now be described.

[0064] <Refractive Index and Abbe Number>

[0065] The refractive index (n) of optical glass d ) and Abbe number (ν d Tested according to the method specified in the national standard GB / T 7962.1—2010.

[0066] In some embodiments, the refractive index (n) of the optical glass of the present invention is... d The lower limit for the refractive index (n) is 1.560, preferably 1.570, and more preferably 1.585. In some embodiments, the refractive index (n) of the optical glass of the present invention is... d The upper limit for the refractive index (n) is 1.640, preferably 1.630, and more preferably 1.620. In some embodiments, the refractive index (n) of the optical glass is... d The range can be 1.560, 1.563, 1.565, 1.567, 1.570, 1.573, 1.575, 1.577, 1.580, 1.583, 1.585, 1.587, 1.590, 1.593, 1.595, 1.597, 1.600, 1.603, 1.605, 1.607, 1.610, 1.613, 1.615, 1.617, 1.620, 1.623, 1.625, 1.627, 1.630, 1.633, 1.635, 1.637, 1.640, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0067] In some embodiments, the Abbe number (ν) of the optical glass of the present invention d The lower limit for the Abbe number (ν) is 43.0, preferably 44.0, and more preferably 45.0. In some embodiments, the Abbe number (ν) of the optical glass of the present invention is... d The upper limit for the Abbe number (ν) is 49.0, preferably 48.0, and more preferably 47.0. In some embodiments, the Abbe number (ν) of the optical glass is... d The range can be 43.0, 43.3, 43.5, 43.7, 44.0, 44.3, 44.5, 44.7, 45.0, 45.3, 45.5, 45.7, 46.0, 46.3, 46.5, 46.7, 47.0, 47.3, 47.5, 47.7, 48.0, 48.3, 48.5, 48.7, 49.0, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0068] <Coefficient of thermal expansion>

[0069] The coefficient of thermal expansion of optical glass (α) -30℃ / 70℃Data for -30℃ to 70℃ were tested according to the method specified in the national standard GB / T7962.16—2010.

[0070] In some embodiments, the coefficient of thermal expansion (α) of the optical glass of the present invention is... -30℃ / 70℃ ) is 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below. In some embodiments, the coefficient of thermal expansion of the optical glass (α) is... -30℃ / 70℃ It can be 90×10 -7 / K、89×10 -7 / K、88×10 -7 / K、87×10 -7 / K、86×10 -7 / K、85×10 -7 / K、84×10 -7 / K、83×10 -7 / K、82×10 -7 / K、81×10 -7 / K、80×10 -7 / K、79×10 -7 / K、78×10 -7 / K、77×10 -7 / K、76×10 -7 / K、75×10 -7 / K、74×10 -7 / K、73×10 -7 / K、72×10 -7 / K、71×10 -7 / K、70×10 -7 / K、69×10 -7 / K, etc., and all ranges and subranges between the above values. It should be understood that, in the implementation, any of the above ranges can be combined with any other range.

[0071] <Stability under water resistance>

[0072] Water resistance stability of optical glass (D) W (Powder method) Tested according to the method specified in the national standard GB / T 17129. In this invention, the stability of water resistance can be simply referred to as water resistance.

[0073] In some embodiments, the water resistance stability (D) of the optical glass of the present invention is... W There are two or more categories, with category 1 being preferred.

[0074] <Stability under acid conditions>

[0075] Acid resistance stability of optical glass (D) A (Powder method) Tested according to the method specified in the national standard GB / T 17129. In this invention, acid resistance stability can be simply referred to as acid resistance.

[0076] In some embodiments, the acid resistance stability (D) of the optical glass of the present invention is... A There are two or more categories, with category 1 being preferred.

[0077] <Weather resistance>

[0078] The weather resistance (CR) test method for optical glass is as follows: The glass sample is placed in a test chamber with a relative humidity of 90% and saturated water vapor. The temperature is alternated between 40℃ and 50℃ every hour for 15 cycles. Weather resistance is classified according to the change in turbidity before and after the sample placement. The weather resistance classification is shown in Table 1.

[0079] Table 1.

[0080]

[0081] In some embodiments, the weather resistance (CR) of the optical glass of the present invention is Class 2 or above, preferably Class 1.

[0082] <Density>

[0083] The density (ρ) of optical glass is tested according to the method specified in the national standard GB / T7962.20—2010.

[0084] In some embodiments, the density (ρ) of the optical glass of the present invention is 3.00 g / cm³. 3 The preferred value is 2.90 g / cm³. 3 The following is a preferred value: 2.80 g / cm³ 3 Below. In some embodiments, the density (ρ) of the optical glass can be 3.00 g / cm³. 3 2.99g / cm 3 2.98g / cm 3 2.97g / cm 3 2.96 g / cm 3 2.95g / cm 3 2.94 g / cm 3 2.93g / cm 3 2.92g / cm 3 2.91 g / cm 3 2.90g / cm 3 2.89 g / cm 3 2.88g / cm 32.87 g / cm 3 2.86 g / cm 3 2.85g / cm 3 2.84 g / cm 3 2.83 g / cm 3 2.82 g / cm 3 2.81 g / cm 3 2.80g / cm 3 2.79 g / cm 3 2.78g / cm 3 2.77 g / cm 3 2.76 g / cm 3 2.75g / cm 3 2.74 g / cm 3 2.73 g / cm 3 2.72 g / cm 3 2.71 g / cm 3 2.70 g / cm 3 2.69 g / cm 3 2.68g / cm 3 2.67 g / cm 3 And so on, as well as all ranges and subranges between the aforementioned values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0085] Knoop Hardness

[0086] Knoop hardness (H) of optical glass K The test was conducted according to the test method specified in the national standard GB / T7962.18-2010. In this invention, Knoop hardness can be simply referred to as hardness.

[0087] In some embodiments, the Knoop hardness (H) of the optical glass of the present invention is... K ) is 530×10 7 Pa or higher, preferably 550 × 10⁻⁶ Pa. 7 Pa or higher, more preferably 570 × 10 Pa 7 Pa or higher. In some embodiments, the Knoop hardness (H) of the optical glass is... K (can be 530×10) 7 Pa, 535×10 7 Pa, 540×10 7 Pa, 545×10 7 Pa, 550×10 7 Pa, 555×10 7 Pa, 560×10 7 Pa, 565×10 7Pa, 570×10 7 Pa, 575×10 7 Pa, 580×10 7 Pa, 585×10 7 Pa, 590×10 7 Pa, etc., and all ranges and subranges between the above values. It should be understood that, in the implementation, any of the above ranges can be combined with any other range.

[0088] <Transition Temperature>

[0089] Transition temperature of optical glass (T) g Test according to the method specified in the national standard GB / T7962.16—2010.

[0090] In some embodiments, the transition temperature (T) of the optical glass of the present invention is... g The temperature is 570°C or below, preferably 560°C or below, and more preferably 520°C to 555°C. In some embodiments, the transition temperature (T) of the optical glass is... g The values ​​can be 520℃, 523℃, 525℃, 527℃, 530℃, 533℃, 535℃, 537℃, 540℃, 543℃, 545℃, 547℃, 550℃, 553℃, 555℃, 557℃, 560℃, 563℃, 565℃, 567℃, 570℃, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0091] <shading>

[0092] The short-wavelength transmission spectral characteristics of the glass of this invention are expressed using colorimetry (λ). 80 λ5) represents λ. 80 λ5 refers to the wavelength corresponding to a glass transmittance of 80%, while λ6 refers to the wavelength corresponding to a glass transmittance of 5%. 80 The measurement was performed using a glass with a thickness of 10 ± 0.1 mm and two optically polished, parallel planes. The spectral transmittance was measured in the wavelength range from 280 nm to 700 nm, and wavelengths exhibiting 80% transmittance were recorded. Spectroscopic transmittance, or transmittance, is the value of transmittance when an intensity I is incident perpendicularly onto the aforementioned surface of the glass. in Light passes through the glass and exits from a plane with an intensity of I. out In the case of light, through I out / I in The quantity represented also includes the transmittance due to surface reflection loss on the aforementioned surfaces of the glass. Similarly, λ₅. In optical glass, λ 80The smaller the value of λ5, the less coloration the glass itself has, and the higher the light transmittance.

[0093] In some embodiments, the tinting strength (λ) of the optical glass of the present invention 80 The tinting strength (λ) of the optical glass is 400 nm or less, preferably 390 nm or less, and more preferably 385 nm or less. In some embodiments, the tinting strength (λ) of the optical glass is... 80 The range can be 370nm, 371nm, 372nm, 373nm, 374nm, 375nm, 376nm, 377nm, 378nm, 379nm, 380nm, 381nm, 382nm, 383nm, 384nm, 385nm, 386nm, 387nm, 388nm, 389nm, 390nm, 391nm, 392nm, 393nm, 394nm, 395nm, 396nm, 397nm, 398nm, 399nm, 400nm, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0094] In some embodiments, the tinting strength (λ5) of the optical glass of the present invention is 360 nm or less, preferably 355 nm or less, and more preferably 350 nm or less. In some embodiments, the tinting strength (λ5) of the optical glass can be 340 nm, 341 nm, 342 nm, 343 nm, 344 nm, 345 nm, 346 nm, 347 nm, 348 nm, 349 nm, 350 nm, 351 nm, 352 nm, 353 nm, 354 nm, 355 nm, 356 nm, 357 nm, 358 nm, 359 nm, 360 nm, etc., as well as all ranges and sub-ranges between the above values. It should be understood that, in embodiments, any of the above ranges can be combined with any other range.

[0095] <wear level>

[0096] Abrasion resistance (F) of optical glass A The wear amount (volume) refers to the ratio of the wear amount of the tested sample to the wear amount (volume) of the standard sample (H-K9 glass) under exactly the same conditions, multiplied by 100. The formula is as follows:

[0097] F A =V / V0×100=(W / ρ) / (W0 / ρ0)×100

[0098] Where: V—volume wear of the tested sample;

[0099] V0—Standard sample volume wear amount;

[0100] W—Mass wear of the tested sample;

[0101] W0—Standard sample mass wear amount;

[0102] ρ—Density of the sample being measured;

[0103] ρ0 — density of the standard sample.

[0104] In some embodiments, the abrasion degree (F) of the optical glass of the present invention A The lower limit for the wear resistance (F) is 110, preferably 115, and more preferably 120. In some embodiments, the wear resistance (F) of the optical glass of the present invention is... A The upper limit for (F) is 145, preferably 140, and more preferably 135. In some embodiments, the abrasion degree (F) of the optical glass is... A The range can be 110, 111, 112, 113, 114, 115, 116, 117, 118, 119, 120, 121, 122, 123, 124, 125, 126, 127, 128, 129, 130, 131, 132, 133, 134, 135, 136, 137, 138, 139, 140, 141, 142, 143, 144, 145, etc., as well as all ranges and subranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0105] Young's Modulus

[0106] Young's modulus (E) is obtained by ultrasonic testing of its longitudinal and transverse wave velocities, and then calculated using the following formula.

[0107]

[0108] G=V S 2 ρ

[0109] In the formula: E is Young's modulus, Pa;

[0110] G is the shear modulus, Pa;

[0111] V T The transverse wave velocity is in m / s;

[0112] V S The longitudinal wave velocity is given in m / s.

[0113] ρ is the density of glass, in g / cm³ 3 .

[0114] In some embodiments, the Young's modulus (E) of the optical glass of the present invention is 86.0 GPa or higher, preferably 90.0 GPa or higher, and more preferably 92.0 GPa or higher. In some embodiments, the Young's modulus (E) of the optical glass can be 86.0 GPa, 86.3 GPa, 86.5 GPa, 86.7 GPa, 87.0 GPa, 87.3 GPa, 87.5 GPa, 87.7 GPa, 88.0 GPa, 88.3 GPa, 88.5 GPa, 88.7 GPa, 89.0 GPa, 89.3 GPa, 89.5 GPa, 89.7 GPa, 90.0 GPa, 90.3 GPa, 99. 0.5 GPa, 90.7 GPa, 91.0 GPa, 91.3 GPa, 91.5 GPa, 91.7 GPa, 92.0 GPa, 92.3 GPa, 92.5 GPa, 92.7 GPa, 93.0 GPa, 93.3 GPa, 93.5 GPa, 93.7 GPa, 94.0 GPa, 94.3 GPa, 94.5 GPa, 94.7 GPa, 95.0 GPa, and all ranges and sub-ranges between the above values. It should be understood that, in the implementation scheme, any of the above ranges can be combined with any other range.

[0115] <Effervescence>

[0116] The bubble degree of optical glass is tested according to the method specified in the national standard GB / T7962.8—2010.

[0117] In some embodiments, the bubble degree of the optical glass of the present invention is grade A or above, preferably grade A0 or above, and more preferably grade A. 00 class.

[0118] <Stripe>

[0119] The method for testing the stripe density of optical glass is as follows: A stripe meter is composed of a point light source and a lens. The stripes are compared with the standard sample from the direction in which they are most easily visible, and classified into four levels according to Table 2.

[0120] Table 2. Rhombus Grading Standards

[0121]

[0122] In some embodiments, the striation of the optical glass of the present invention is grade D or higher, preferably grade C or higher, and more preferably grade B or higher.

[0123] [Manufacturing methods for optical glass]

[0124] The manufacturing method of the optical glass of this invention is as follows: The glass of this invention is produced using conventional raw materials and processes, including but not limited to using oxides, hydroxides, complex salts (such as carbonates, nitrates, sulfates, etc.), boric acid, etc. as raw materials. After the raw materials are prepared according to conventional methods, the prepared furnace charge is put into a melting furnace (such as a platinum or platinum alloy crucible) at 1150℃~1400℃ for melting. After clarification and homogenization, a homogeneous molten glass without undissolved substances is obtained. This molten glass is then cast in a mold and annealed. Those skilled in the art can appropriately select raw materials, process methods, and process parameters according to actual needs.

[0125] [Glass prefabrication and glass components]

[0126] Glass preforms can be manufactured from the produced optical glass using methods such as direct drop forming, grinding, or hot pressing. Specifically, glass preforms can be manufactured by directly and precisely drop-forming molten optical glass into precision glass preforms, or by machining such as grinding and polishing, or by hot pressing a preform made from optical glass for compression molding followed by grinding. It should be noted that the methods for preparing glass preforms are not limited to the methods described above.

[0127] As described above, the optical glass of the present invention is useful for various glass components and optical designs. It is particularly preferred to form a preform from the optical glass of the present invention, and to use the preform for hot pressing, precision stamping, etc., to manufacture glass components such as lenses and prisms.

[0128] Both the glass preform and the glass element of the present invention are formed from the optical glass described above. The glass preform of the present invention possesses the excellent properties of optical glass; the glass element of the present invention possesses the excellent properties of optical glass, and can provide various lenses, prisms, and other glass elements with high optical value.

[0129] Examples of lenses include concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, plano-concave lenses, and so on, where the lens surface is spherical or aspherical.

[0130] [equipment]

[0131] The optical glass of this invention, or the glass element formed from the optical glass, can be used to manufacture devices such as photographic equipment, video equipment, projection equipment, display equipment, vehicle-mounted equipment, monitoring equipment, AR (augmented reality) equipment, MR (mixed reality) equipment, VR (virtual reality) equipment, and mobile electronic devices (such as mobile phones, watches, etc.).

[0132] Example

[0133] <Example of Optical Glass>

[0134] To further illustrate and explain the technical solution of the present invention, the following non-limiting embodiments are provided.

[0135] In this embodiment, optical glass with the composition shown in Tables 3 to 5 was obtained by using the above-described optical glass manufacturing method, and the performance of each glass was measured by the test method described in this invention. The measurement results are shown in Tables 3 to 5.

[0136] Table 3.

[0137]

[0138]

[0139] Table 4.

[0140]

[0141]

[0142] Table 5.

[0143]

[0144]

[0145] <Example of Glass Prefabricated Components>

[0146] The glass obtained from optical glass examples 1# to 15# is used to manufacture preforms of various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses, by means of grinding, hot pressing, precision stamping, or other molding methods.

[0147] <Example of Glass Component>

[0148] Annealing the preforms obtained from the above glass preform examples reduces the internal stress of the glass while fine-tuning the refractive index, so that the optical properties such as the refractive index reach the desired values.

[0149] Next, the prefabricated parts are ground and polished to produce various lenses and prisms, such as concave meniscus lenses, convex meniscus lenses, biconvex lenses, biconcave lenses, plano-convex lenses, and plano-concave lenses. An anti-reflective film can also be coated on the surface of the resulting glass elements.

[0150] <Equipment Example>

[0151] The glass elements obtained from the above-described glass element embodiments are optically designed to form optical components or assemblies by using one or more glass elements, and are thus assembled in various devices, such as imaging devices, monitoring devices, sensors, microscopes, medical technology, digital projection, communications, optical communication technology / information transmission, optics / lighting in the automotive field, photolithography, excimer lasers, wafers, computer chips, as well as integrated circuits and electronic devices including such circuits and chips, mobile phones, etc.

[0152] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0153] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. Optical glass, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 42.5%–54%; B2O3: 5.5%–17.5%; TiO2: 3%–15%; ZnO: 0.1%–8%; Na2O: 2%–14%; CaO: 6%–18%, of which (CaO+B2O3) / SiO2 is 0.28–0.

80.

2. The optical glass according to claim 1, characterized in that, Its components, expressed as a weight percentage, also contain: Li2O: 0–7%; and / or K2O: 0–7%; and / or MgO: 0–5%; and / or SrO: 0–5%; and / or BaO: 0–5%; and / or ZrO2: 0–5%; and / or Al2O3: 0–6%; and / or Nb2O5: 0–3%; and / or WO3: 0–3%; and / or Ln2O3: 0–3%; and / or clarifying agent: 0–1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

3. Optical glass, characterized in that, Its composition includes SiO2, B2O3, TiO2, ZnO, Na2O, and CaO, expressed as a weight percentage, wherein (CaO+B2O3) / SiO2 is 0.28–0.80, and the refractive index n of the optical glass is... d The Abbe number ν ranges from 1.560 to 1.

640. d Its S value is 43.0–49.0, and its Knoop hardness is 530 × 10⁻⁶. 7 Above Pa, chromaticity λ 80 The wavelength is below 400nm, and the chromaticity λ5 is below 360nm.

4. The optical glass according to claim 3, characterized in that, Its composition, expressed as a weight percentage, contains: SiO2: 42.5%–54%; and / or B2O3: 5.5%–17.5%; and / or TiO2: 3%–15%; and / or ZnO: 0.1%–8%; and / or Na2O: 2%–14%; and / or CaO: 6%–18%; and / or Li2O: 0%–7%; and / or K2O: 0%–7%; and / or MgO: 0%–5%; and / or SrO: 0%–5%. ; and / or BaO: 0-5%; and / or ZrO2: 0-5%; and / or Al2O3: 0-6%; and / or Nb2O5: 0-3%; and / or WO3: 0-3%; and / or Ln2O3: 0-3%; and / or clarifying agent: 0-1%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

5. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as a weight percentage and satisfy one or more of the following conditions: 1) The ratio of (CaO+B2O3) / SiO2 is 0.35 to 0.75, preferably 0.40 to 0.65; 2) The CaO / B2O3 ratio is 0.40 to 2.50, preferably 0.50 to 2.00, more preferably 0.60 to 1.60, and even more preferably 0.80 to 1.20; 3) The CaO / TiO2 ratio is 0.50 to 3.00, preferably 0.60 to 2.80, more preferably 0.80 to 2.00, and even more preferably 1.00 to 1.60; 4) The ratio of (ZnO+BaO+SrO) / B2O3 is 0.05 to 1.00, preferably 0.10 to 0.80, and more preferably 0.15 to 0.

50. 5) The ratio of (ZrO2+Nb2O5+WO3) / ZnO is 1.00 or less, preferably 0.70 or less, and more preferably 0.05 to 0.

50. 6) The ratio of (Li2O+Na2O+K2O) / TiO2 is 0.30~4.00, preferably 0.50~3.00, more preferably 0.80~2.50, and even more preferably 1.00~1.80; 7) The ratio of (Li2O+Na2O+K2O) / CaO is 0.30~2.50, preferably 0.50~2.00, more preferably 0.60~1.60, and even more preferably 0.80~1.20; 8) The ratio of (ZnO+BaO+SrO+MgO) / SiO2 is 0.01 to 0.40, preferably 0.03 to 0.30, and more preferably 0.05 to 0.15; 9) The Li2O / Al2O3 ratio is 0.05 to 5.00, preferably 0.10 to 3.00, and more preferably 0.50 to 1.50; 10) (TiO2+ZnO) / (Li2O+K2O) is 1.00~6.00, preferably (TiO2+ZnO) / (Li2O+K2O) is 1.50~5.00, more preferably (TiO2+ZnO) / (Li2O+K2O) is 2.00~4.50, and even more preferably (TiO2+ZnO) / (Li2O+K2O) is 2.50~4.

00.

6. The optical glass according to any one of claims 1 to 4, characterized in that, Its components are expressed as weight percentages, wherein: SiO2: 44%–52%, preferably SiO2: 46%–49.5%; and / or B2O3: 8%–16%, preferably B2O3: 10.5%–14.5%; and / or TiO2: 5%–14%, preferably TiO2: 7%–12%; and / or ZnO: 1%–7%, preferably ZnO: 2%–5%; and / or Li2O: 0.1%–4.5%, preferably Li2O. 0.5%–3.5%; and / or Na2O: 4%–12%, preferably Na2O: 6%–9.8%; and / or K2O: 0.1%–4.5%, preferably K2O: 0.5%–3.5%; and / or MgO: 0%–3%, preferably MgO: 0%–2%, more preferably MgO-free; and / or CaO: 8%–16%, preferably CaO: 10.1%–14.5%; and / or SrO: 0%–3%, preferably SrO: 0%–3%. ~2%, more preferably free of SrO; and / or BaO: 0~3%, preferably BaO: 0~2%, more preferably free of BaO; and / or ZrO2: 0~3%, preferably ZrO2: 0.1%~2%; and / or Al2O3: 0.1%~4.5%, preferably Al2O3: 0.5%~3.5%; and / or Nb2O5: 0~2%, preferably Nb2O5: 0~1%, more preferably free of Nb2O5; and / or WO3 0-2%, preferably WO3; 0-1%, more preferably WO3-free; and / or Ln2O3: 0-2%, preferably Ln2O3; 0-1%, more preferably Ln2O3-free; and / or clarifying agent: 0-0.5%, preferably 0-0.3%, wherein the Ln2O3 is one or more of La2O3, Gd2O3, Y2O3, and Yb2O3, and the clarifying agent is one or more of Sb2O3, SnO2, and CeO2.

7. The optical glass according to any one of claims 1 to 4, characterized in that, The refractive index n of the optical glass d The value is 1.560–1.640, preferably 1.570–1.630, more preferably 1.585–1.620; and / or the Abbe number ν. d The value is 43.0 to 49.0, preferably 44.0 to 48.0, more preferably 45.0 to 47.0; and / or the chromaticity λ 80 The wavelength is 400 nm or less, preferably 390 nm or less, more preferably 385 nm or less; and / or the tinting strength λ5 is 360 nm or less, preferably 355 nm or less, more preferably 350 nm or less; and / or the Knoop hardness is 530 × 10⁻⁶. 7 Pa or higher, preferably 550 × 10⁻⁶ Pa. 7 Pa or higher, more preferably 570 × 10 Pa 7 Pa or above; and / or coefficient of thermal expansion α -30℃ / 70℃ 90×10 -7 / K or less, preferably 80×10 -7 / K or less, preferably 75×10 -7 / K or below; and / or water resistance stability of Class 2 or above, preferably Class 1; and / or acid resistance stability of Class 2 or above, preferably Class 1; and / or weather resistance of Class 2 or above, preferably Class 1; and / or density of 3.00 g / cm³. 3 The preferred value is 2.90 g / cm³. 3 The following is a preferred value: 2.80 g / cm³ 3 The following are also considered: a transition temperature of 570°C or less, preferably 560°C or less, more preferably 520°C to 555°C; an abrasion degree of 110 to 145, preferably 115 to 140, more preferably 120 to 135; a Young's modulus of 86.0 GPa or more, preferably 90.0 GPa or more, more preferably 92.0 GPa or more; and / or a bubble degree of A grade or more, preferably A0 grade or more, more preferably A 00 Grade; and / or stripe density of grade D or above, preferably grade C or above, more preferably grade B or above.

8. A glass precast component, characterized in that, It is made of the optical glass described in any one of claims 1 to 7.

9. A glass element, characterized in that, It is made of the optical glass described in any one of claims 1 to 7, or of the glass preform described in claim 8.

10. A device, characterized in that, It contains the optical glass according to any one of claims 1 to 7, and / or contains the glass element according to claim 9.